A pepducin derived from the third intracellular loop of FPR2 is a partial agonist for direct activation of this receptor in neutrophils but a full agonist for cross-talk triggered reactivation of FPR2. - Michael Gabl; Malene Winther; Sarah Line Skovbakke; Johan Bylund; Claes Dahlgren; Huamei Forsman (PLoS ONE, 2014)
We recently described a novel receptor cross-talk mechanism in neutrophils, unique in that the signals generated by the PAF receptor (PAFR) and the ATP receptor (P2Y2R) transfer formyl peptide receptor 1 (FPR1) from a desensitized (non-signaling) state back to an actively signaling state (Forsman H et al., PLoS One, 8:e60169, 2013; Önnheim K, et al., Exp Cell Res, 323∶209, 2014). In addition to the G-protein coupled FPR1, neutrophils also express the closely related receptor FPR2. In this study we used an FPR2 specific pepducin, proposed to work as an allosteric modulator at the cytosolic signaling interface, to determine whether the cross-talk pathway is utilized also by FPR2. The pepducin used contains a fatty acid linked to a peptide sequence derived from the third intracellular loop of FPR2, and it activates as well as desensensitizes this receptor. We now show that neutrophils desensitized with the FPR2-specific pepducin display increased cellular responses to stimulation with PAF or ATP. The secondary PAF/ATP induced response was sensitive to FPR2-specific inhibitors, disclosing a receptor cross-talk mechanism underlying FPR2 reactivation. The pepducin induced an activity in naïve cells similar to that of a conventional FPR2 agonist, but with lower potency (partial efficacy), meaning that the pepducin is a partial agonist. The PAF- or ATP-induced reactivation was, however, much more pronounced when neutrophils had been desensitized to the pepducin as compared to cells desensitized to conventional agonists. The pepducin should thus in this respect be classified as a full agonist. In summary, we demonstrate that desensitized FPR2 can be transferred back to an actively signaling state by receptor cross-talk signals generated through PAFR and P2Y2R, and the difference in agonist potency with respect to pepducin-induced direct receptor activation and cross-talk reactivation of FPR2 puts the concept of functional selectivity in focus.